Staining pattern of type IV collagen and prognosis in early stage adenocarcinoma of the lung. Issue 7 (July 1994) - Watanabe, N; Nakajima, I; Abe, S; Ogura, S; Isobe, H; Kawakami, Y
Abstract : AIMS--To examine the prognostic value of basement membrane expression in early stage adenocarcinoma of the lung. METHODS--Using antibodies to type IV collagen, basement membrane expression at the tumour-stromal border was immunohistochemically analysed in 30 patients with early stage adenocarcinoma of the lung (pstage I and pstage II). Two patterns of staining for type IV collagen were observed: in the first one the staining line was conserved or partially fragmented; in the second the staining line was widely fragmented or absent in more than 10% of the tumour area. The first staining pattern was categorised as continuous and the second as discontinuous. RESULTS--Of the 24 patients with pstage I adenocarcinoma, 12 (50%) cases showed a continuous pattern. In only one (16.7%) of the six patients with pstage II adenocarcinoma was this pattern evident. Five year survival was greater in pstage I adenocarcinoma (65%) than in pstage II adenocarcinoma (17%), but the difference was not significant. When the analysis was restricted to the 24 patients with pstage I adenocarcinoma, five year survival was better in continuous pattern cases (88%) than in discontinuous pattern cases (20.5%) (p < 0.05). The survival curve of 12 patients with pstage I adenocarcinoma and a discontinuous pattern resembled that of the six patients with pstage II adenocarcinoma. CONCLUSION--These findings suggest that patients with pstage I adenocarcinoma and a discontinuous pattern have histopathologically unrecognised micrometastasis when they come to surgery. The staining pattern of type IV collagen could help in the prognosis of pstage I adenocarcinoma of the lung after surgery.